Financial and Pension Literacy and Retirement Preparedness in Sri Lanka: Evidence from Employee Provident Fund Contributors - Tiyani Rodrigo; Hyungsoo Kim (Journal of Consumer Sciences, 2023)
Sri Lanka has a rapidly aging population in South Asia, but little attention is given to financial preparedness for retirement. This study expects to provide an overview of the current retirement system in Sri Lanka and investigate financial and pension literacy's role in retirement preparedness. This study administered an online survey to study retirement preparedness subjectively (n = 142) and objectively (n = 115) among the EPF contributors. This non-experimental study uses an online survey to assess financial and pension literacy's roles in retirement preparedness. This study used ordered logistic (Ologit) regressions and ordinary least squares (OLS) regressions to test the two hypotheses. Results indicate a positive and statistically significant association between financial (only objective measure) and pension literacy and retirement preparedness. However, another study shows no synergy effect between financial and pension literacy. Conclusively, drawing policymakers' attention to diversifying EPF investments, including financial and pension literacy concepts in workplace workshops and studying pension literacy and retirement preparedness in different samples.